2014
DOI: 10.2174/1874364101408010019
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Growth of Lens Epithelial Cells from Cataract Patients - Association with Possible Risk Factors for Posterior Capsule Opacification

Abstract: Aim : Inter-individual differences in intrinsic proliferative capacity of lens epithelial cells may have importance for the risk of developing posterior capsule opacification (PCO) after cataract surgery. The purpose of the present study was to determine growth of human lens epithelial cells (HLEC) in culture and investigate possible associations with clinical characteristics of the donors, such as age, sex, pseudoexfoliation, uveitis and diabetes.Methods : Pieces of lens capsule and adhering lens epithelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 43 publications
1
13
1
Order By: Relevance
“…Even though we have observed a slightly higher rate of cell growth in capsule-epithelium specimens derived from female cataract patients, 32 no difference in results were seen between cells from different genders in our previous study of estrogen effects. Therefore, HLECs, only derived from women over 60 years undergoing cataract surgery, were used in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…Even though we have observed a slightly higher rate of cell growth in capsule-epithelium specimens derived from female cataract patients, 32 no difference in results were seen between cells from different genders in our previous study of estrogen effects. Therefore, HLECs, only derived from women over 60 years undergoing cataract surgery, were used in this study.…”
Section: Discussioncontrasting
confidence: 84%
“…Several factors might account for this finding, such as the surgical procedure or a potentially high intrinsic proliferative capacity of the lens epithelial cells in some patients. 26 Likewise, the IOL material and design might have influenced this significantly, 27 although previous studies evaluating the bifocal IOL based on the same diffractive platform have not shown this rate of proliferative forms of PCO. 15 In conclusion, the trifocal diffractive IOL evaluated can provide effective distance, intermediate, and near visual restoration after cataract surgery during a 12-month follow-up, with good levels of visual quality.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be because the lens capsule is primarily composed of Type IV collagen, and it is sufficiently elastic to handle the accommodation range in this study. Although female gender was correlated with an increased rate of epithelial cell proliferation, no significant correlation was identified between gender and the ALCC in this study [ 13 ]. This finding may be because we only included normal subjects in the current study.…”
Section: Discussionmentioning
confidence: 76%